The Holy Reich Nazi conceptions of Christianity, 1919-1945 - Steigmann-Gall, Richard (Cambridge University Press, 2003)
Analyzing the previously unexplored religious views of the Nazi elite, Richard Steigmann-Gall argues against the consensus that Nazism as a whole was either unrelated to Christianity or actively opposed to it. He demonstrates that many participants in the Nazi movement believed that the contours of their ideology were based on a Christian understanding of Germany's ills and their cure. A program usually regarded as secular in inspiration - the creation of a racialist 'people's community' embracing antisemitism, antiliberalism and anti-Marxism - was, for these Nazis, conceived in explicitly Christian terms. His examination centers on the concept of 'positive Christianity,' a religion espoused by many members of the party leadership. He also explores the struggle the 'positive Christians' waged with the party's paganists - those who rejected Christianity in toto as foreign and corrupting - and demonstrates that this was not just a conflict over religion, but over the very meaning of Nazi ideology itself